2013
DOI: 10.5935/0103-507x.20130054
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-induced lung injury in preterm infants

Abstract: In preterm infants, the need for intubation and mechanical ventilation is associated with ventilator-induced lung injuries and subsequent bronchopulmonary dysplasia. The aim of the present review was to improve the understanding of the mechanisms of injury that involve cytokine-mediated inflammation to contribute to the development of new preventive strategies. Relevant articles were retrieved from the PubMed database using the search terms "ventilator-induced lung injury preterm", "continuous positive airway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 50 publications
0
34
0
9
Order By: Relevance
“…This process of bronchoalveolar and vascular maturation of the lungs can be altered at any moment, leading to chronic complications that begin in the neonatal period (neonatal chronic pulmonary disease) or later in the life cycle. Some known factors in the development of these problems are prematurity, use of supplementary oxygen, ventilatory support, infection, late implementation of enteral nutrition, and patent ductus arteriosus 12,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process of bronchoalveolar and vascular maturation of the lungs can be altered at any moment, leading to chronic complications that begin in the neonatal period (neonatal chronic pulmonary disease) or later in the life cycle. Some known factors in the development of these problems are prematurity, use of supplementary oxygen, ventilatory support, infection, late implementation of enteral nutrition, and patent ductus arteriosus 12,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of ventilatory support and prolonged oxygen use in the neonatal period, especially in premature newborns with gestational age less than 30 weeks, is related to the appearance of bronchopulmonary dysplasia 11,12 . Various studies have also found that premature newborns that received mechanical ventilation (MV) during the neonatal period showed greater risk of developing respiratory diseases like asthma and pneumonia in early childhood when compared to those that did not receive MV 13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Progressive and high-frequency respiratory insufficiency, breathlessness due to immaturity and atelectasis of the lungs characterize the RDSNB. It is reported that although it has been linked to a qualitative and quantitative dysfunction of the pulmonary surfactant system, its replacement has been associated with a sustained improvement in lung function and a reduction in the mortality rate [3].…”
Section: Introductionmentioning
confidence: 99%
“…Alguns deles servem como estímulo ao crescimento normal dos maxilares (hábitos bucais nutritivos), outros estão associados ao crescimento ósseo alterado, os denominados deletérios (hábitos bucais não nutritivos), que são considerados fatores etiológicos da maloclusão Bastos, 1995;Paulsson et al, 2004;Ferrini et al, 2007;Garbin et al, 2014;Neiva et al, 2014). Desde a vida intrauterina, o feto apresenta o reflexo natural de sucção não nutritiva, por meio das mãos e dedos, pois a sucção não nutritiva proporciona à criança diversas sensações como bem-estar, prazer emocional e proteção, dentre outras (Garbin et al, 2014 Bancalari, 2009;Lista et al, 2010;Pfister;Soll, 2012;Carvalho et al, 2013;Schmalisch et al, 2014). Em relação ao peso, a DBP apresenta incidência elevada entre os RNPT, particularmente aqueles de MBP.…”
Section: Descritoresunclassified
“…A função do CPAP é, principalmente, estabilizar as vias aéreas, melhorar a função pulmonar e reduzir as crises de apneia (Hascoet et al, 2008;Claure, 2013;Carvalho et al, 2013). O CPAP deve ser aplicado, de preferência, por meio de "prongs" nasal, sendo um método simples, não invasivo e barato (Sankar et al, 2008;Carlisle et al, 2010;Ota et al, 2013).…”
Section: Descritoresunclassified